Redistribution of Direct Payments to Permanent Grasslands: Intended and Unintended Impacts. (26th October 2015) - Hecht, Judith; Moakes, Simon; Offermann, Frank
Summary: Grasslands are an important landscape element in Europe. However, the grassland area has been reduced in the last 50 years. This article assesses potential impacts of a scenario that redistributes CAP direct payments to maintain or increase permanent grassland areas using a farm‐level modelling approach in Germany, Wales and Switzerland. Our results indicate that a reallocation of support payments can help to prevent abandonment or conversion of permanent grassland to more intensive land use. This may be more difficult to achieve when there is a limited arable area to transfer budget from, as demonstrated by results in Wales. Policy effects at the level of farm type can often vary due to the heterogeneities and complexities of permanent grassland farming systems. Our results also show that unintended 'slippage' effects such as increased temporary grassland area may occur, though this could also be seen as a form of sustainable intensification. Other difficulties include: a) potential for negative effects on specific farm types despite a positive overall effect, and b) distortions within land markets due to the attractiveness of support payments within sectors of low profitability. Abstract : Grasslands are an important landscape element in Europe. However, the grassland area has been reduced in the last 50 years. This article assesses potential impacts of a scenario that redistributes CAP direct payments to maintain or increase permanent grassland areas using a farm‐level modelling approach in Germany, Wales and Switzerland. Our results indicate that a reallocation of support payments can help to prevent abandonment or conversion of permanent grassland to more intensive land use.